2023
DOI: 10.3390/agronomy13092271
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Selenium Endows Salt-Tolerant and Salt-Sensitive Soybeans with Salt Tolerance through Plant-Microbial Coactions

Yin Wang,
Chao Xu,
Hada Wuriyanghan
et al.

Abstract: Soil salinization is a common abiotic stress that seriously affects soybean growth and yield, underscoring the need to enhance plant salt tolerance for sustainable agriculture development. Selenium is a beneficial element that has been shown to promote plant growth, development and stress resistance. This study employed pot experiments to investigate the effects of different salt levels (0, 50, 100 and 150 mM NaCl) on salt-tolerant (Zhonghuang 13) and salt-sensitive soybean (Dongnong 63) varieties. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…MIR159 expression is induced in peanut by salt stress, and miR159 regulates the expression of its target genes [26]. In addition, miR159 in different tissues of S. portulacastrum is involved in plant responses to high-salt stress [27]. In the current study, qRT-PCR results showed that MIR159 responds to high-NaCl concentrations in soybean (Figure 4).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…MIR159 expression is induced in peanut by salt stress, and miR159 regulates the expression of its target genes [26]. In addition, miR159 in different tissues of S. portulacastrum is involved in plant responses to high-salt stress [27]. In the current study, qRT-PCR results showed that MIR159 responds to high-NaCl concentrations in soybean (Figure 4).…”
Section: Discussionsupporting
confidence: 52%
“…MiR159 responds to high-salt stress in S. portulacastrum [6,27]. We therefore used qRT-PCR to measure the transcript levels of MIR159 family genes in leaves and roots of soybean plants subjected to short-term (6 h) treatment with 200 mM NaCl.…”
Section: Responses Of the Soybean Mir159 Gene Family To Salt Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Salt stress is a detrimental environmental factor known to impede plant growth and development significantly [23]. To circumvent the deleterious effects of such stress, plants have evolved complex regulatory mechanisms that include the modulation of gene expression [3,24,25]. Notably, the impact of salt stress on the NAC gene family in Cyclocarya paliurus, a species of considerable ecological significance, remains underexplored.…”
Section: Introductionmentioning
confidence: 99%